HUBUNGAN GAYA KELEKATAN DENGAN KECENDERUNGAN NEUROTICISM PADA INDIVIDU YANG SEDANG MENJALIN HUBUNGAN ROMANTIS - Utami, Made Silvana Dwi (University of Surabaya, 2016)
The closeness of romantic relationships are not always viewed positively so as to showed of negative impacts in romantic relationship. The negative impact of a romantic relationship is dependence and anxiety that is based on the private individuals who have a tendency to neuroticism. In the previous study found that the ambivalent and avoidant attachment style is a predictor as emergence tendency of neuroticism. The purpose of this study was to determine the relationship between ambivalent and avoidant attachment style with a tendency to neuroticism in individuals who are in a romantic relationship. Subjects in this study were students of the Faculty of Psychology, Surabaya University, which currently is in a romantic relationship for at least one month. Research subjects were taken as many as 105 people were selected by incidental sampling technique. Analysis technique used by Pearson correlation technique with software SPSS 16. The results showed that there was a positive correlation between ambivalent and avoidant attachment style with tendencyof neuroticism in individuals who are in a romantic relationship (p = 0.000 and 0.029), higherambivalent attachment style or avoidant attachment style, the higher the tendency of neuroticism in individuals who are in a romantic relationship. In this study, the subject of the study had the ambivalent and avoidant attachment style are moderate and the level tendency of neuroticism that is also being moderate.